2015
DOI: 10.1051/0004-6361/201526501
|View full text |Cite
|
Sign up to set email alerts
|

Wide-field LOFAR imaging of the field around the double-double radio galaxy B1834+620

Abstract: Context. The existence of double-double radio galaxies (DDRGs) is evidence for recurrent jet activity in active galactic nuclei (AGN), as expected from standard accretion models. A detailed study of these rare sources provides new perspectives for investigating the AGN duty cycle, AGN-galaxy feedback, and accretion mechanisms. Large catalogues of radio sources, on the other hand, provide statistical information about the evolution of the radio-loud AGN population out to high redshifts. Aims. Using wide-field i… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
26
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
2

Relationship

5
3

Authors

Journals

citations
Cited by 35 publications
(26 citation statements)
references
References 52 publications
(81 reference statements)
0
26
0
Order By: Relevance
“…O' Dea et al (2001) have classified 3C 236 as a doubledouble (Saikia & Jamrozy 2009;Orrù et al 2015) radio galaxy, since the restarted activity in the core has extended emission aligned with the large-scale lobes. Then, 3C 236 may be a "triple-double" radio galaxy; the inner hotspot in the NW lobe signifying a stall in the jet, or a short sputter in the accretion episode responsible for the creation of the large-scale lobes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…O' Dea et al (2001) have classified 3C 236 as a doubledouble (Saikia & Jamrozy 2009;Orrù et al 2015) radio galaxy, since the restarted activity in the core has extended emission aligned with the large-scale lobes. Then, 3C 236 may be a "triple-double" radio galaxy; the inner hotspot in the NW lobe signifying a stall in the jet, or a short sputter in the accretion episode responsible for the creation of the large-scale lobes.…”
Section: Discussionmentioning
confidence: 99%
“…Also, Cantwell et al (submitted) studied NGC 6251 and found ages raging from 50 Myr to greater than 200 Myr. Orrù et al (2015) have studied the famous doubledouble GRG B1864+620 and showed that the source ages derived for its outer pair of radio lobes indicate that the AGN activity has stopped in the recent past.…”
Section: Introductionmentioning
confidence: 99%
“…For a few double-double radio sources, spectral ageing modelling, based on equipartition assumptions, has provided estimates of the duration of the quiescent phase, which is found to be in the range 0.1∼10 Myr. This is usually at least a factor two shorter than the first active phase, which is observed to be of the order of a few tens up to a few hundreds of million years (Konar et al 2012Orrù et al 2015;Nandi et al 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Major steps forward in the selection and study of restarted radio galaxies have recently been allowed by the advent of the LOw Frequency ARray (LOFAR,van Haarlem et al 2013) through its unprecedented sensitivity and resolution at low frequency, where the remnant lobes are expected to be brighter (see e.g. Shulevski et al 2015;Orrù et al 2015;Brienza et al 2018;Mahatma et al 2019;Jurlin et al 2020;Shabala et al 2020) However, there is one peculiar class of restarted radio galaxies that we may still be missing:. sources showing the footprint of their multi-epoch activity through spatial variations of their spectral index across their radio lobes.…”
Section: Introductionmentioning
confidence: 99%
“…Despite this there is a growing number of polarised sources being found at low frequencies (e.g. Bernardi et al 2013;Mulcahy et al 2014;Jelić et al 2015;Orrù et al 2015;Lenc et al 2016;Van Eck et al 2018;O'Sullivan et al 2018;Neld et al 2018;Riseley et al 2018). J1235+5317 was discovered to be polarised at 144 MHz by Van Eck et al (2018), in LOFAR data imaged at an angular resolution of 4.3 .…”
Section: Introductionmentioning
confidence: 99%